Temporal and diurnal analysis of trace elements in the Cryospheric water at remote Laohugou basin in northeast Tibetan Plateau. (March 2017) - Dong, Zhiwen; Kang, Shichang; Qin, Dahe; Qin, Xiang; Yan, Fangping; Du, Wentao; Wei, Ting
Abstract: An evaluation of glacial meltwater chemistry is needed under recent dramatic glacier melting when water resources might be significantly impacted. This study investigated trace elements variation in the meltwater stream, and its related aquatic environmental information, at the Laohugou (LHG) glacier basin (4260 m a.s.l.) at a remote location in northeast Tibetan Plateau. We focused on the spatial, temporal and diurnal change of trace elements during the glacier ablation period. Results showed evident elements spatial difference on the glacier surface meltwater, as most of the elements showed increased concentration at the terminus compared to higher elevations sites. Dominant elements in the meltwater were Ba, Sr and Cr, whereas elements with high enrichment factors (EFs) were Sb, Ni, Mo and Zn. Temporal change of some trace elements concentration (e.g. Sc, Cu, and Rb) indicated increasing trend with accelerated snow-ice melting, whereas others (e.g. Ni, Zn, and Pb) showed decreasing trend. We find that, trace elements showed evident diurnal change and a peak value of concentration was observed each day at about 15:00–17:00, and the diurnal change was influenced by runoff level and pH. Moreover, EFs calculations revealed that heavy metals were partially originated from regional anthropogenic sources. Overall, the accelerated diurnal and temporal snow-ice melting (with high runoff level) were correlated to increased elemental concentration, pH, EC and elemental change mode, and thus this work is of great importance for evaluating the impacts of accelerated glacier melting to meltwater chemistry and downstream ecosystem in the northeast Tibetan Plateau. Highlights: New data were presented on temporal and diurnal change of trace elements in Cryospheric water. Trace elements showed evident diurnal change with a peak concentration at about 15:00–17:00. Diurnal change of trace elements was influenced by runoff level and pH. Heavy metals (e.g. Ni, Zn, Mo, Sb and Pb) were partially from anthropogenic sources.